An Effect of Gamification on Education under Online Lives Teching - Na Lamphun, Phannachet; Qu, Jian; Preelakha, Pornsak (INTERNATIONAL SCIENTIFIC JOURNAL OF ENGINEERING AND TECHNOLOGY (ISJET), 2020)
It is necessary for traditional offline teaching to be transformed into online teaching to continue education during emergencies. The technology is ready for the transition of teaching from traditional classes to online classes. However, it is difficult to achieve successful online live teaching due to several factors, including distraction, motivation, and self-directed learning of the learner. Therefore, gamification has been selected to apply to online live teaching. By applying the game mechanic including game and reward system, this motivates the learners and increases their participation. The result illustrates that gamification can help increase participation and motivate learners in online teaching compared to in-class teaching. Moreover, by extending the research to apply gamification to pure online lives teaching, the result shows that it is guaranteed to help motivate the learners to attend the classes, participate in activities, and make discussions, thus increasing the understanding of course materials reflected by the activities and quiz scores. This fact shows that gamification is necessary for online live teaching which can help support motivation and increase participation in online live class learning.